Development of a Scale to Measure Personal Growth After Experiencing a Sibling's Hospitalization and One's Mother Rooming-in with the Sibling - FUJIWARA, Chieko; YAMADA, Akiko; KURAHASHI, Rika; NIINOMI, Kazuteru (JOURNAL OF JAPAN HEALTH MEDICINE ASSOCIATION, 2016)
Objective: To identify mothers' ratings of the structure of personal growth in children whose sibling is hospitalized and whose mother subsequently rooms-in with the sibling. We also developed and evaluated the reliability and validity of a scale to assess this type of growth. Methods: We obtained consent to conduct our research at 63 medical institutions in Japan, and the anonymous self-administered questionnaire was answered by the mothers of children with a hospitalized sibling. Participants rated on a 4-point Likert scale 26 items that were identified from content analysis in a previous study as being indicative of children's positive changes. Exploratory factor analysis was performed and the scale's structure was identified, and the reliability and validity evaluated. Results: Participants (N=254) with siblings aged between 2 and 18 years were analyzed. After factor analysis, the measure, which we named the Siblings' Personal Growth Scale (SPGS), comprised 22 items divided across three factors of altruistic behavior, development of emotional and social skills, and self-control, and the scale's structure was identified. Cronbach's coefficient alpha value indicated high reliability (.897-.940), and the Kaiser-Meyer-Olkin value (.940) and Bartlett's test of sphericity were significant (p<.001), supporting the sampling adequacy. The content validity was confirmed by a research team comprising experts in pediatric nursing and clinical psychology. The criterion-related validity was evaluated by a Pearson product-moment correlation coefficient comparison between the SPGS and the internal behavior subscale of the Child Behavior Checklist/4-18. It was found to be significant at .217 (p=.029) for males aged between 4 and 11 years, but not for any other groups. Conclusions: The structure of the SPGS was identified and the future feasibility of the scale supported.